KEHIDUPAN SOSIAL EKONOMI PETANI JAGUNG DI KENAGARIAN KAMPUNG TANGAH BATU HAMPAR KECAMATAN LUBUK BASUNG KABUPATEN AGAM TAHUN 1996-2012 - Agnesia, Thari; Zusmelia, Zusmelia; Kharles, Kharles (Pendidikan Sejarah, 2013)
ABSTRACTÂ This Thesis discusses about the existence of corn farmers in Kenagarian Kampung Tangah, Sub distric Lubuk Basung, Agam Regency, 1996-2012. The formulation of the problem in this research is 1) How social economic life of the society before maize agriculture, 2) Why the people prefer to plant corn, 3) The impact of corn on the social economic life of the society. As a study of the social economic history, This thesis aims to look at the effect of maize on the social economic life of the society in Kenagarian Kampung Tangah. This research includes the study of history with the following research methods. 1) Heuristics that divorce and collect information from primary and secondary sources, 2) Criticism of sources including internal and external criticims namely by testing for the authen ticity of the sources or material specified, 3) Interpretation which is a reinterpretation of activity data that has been collected, 4) Historiographi is writins a stage presentation thesis. From the resuit of this study concluded that the planting of the corn crop farmers can goost the economic in Kenagarian Kampung Tangah As for the impact of which is feit by farmers : 1) Before the corn farming community in Kenagarian Kampung Tangah are rice farmers, in addition they also heve another job to support his familyâs needs, 2) the reasons of farmers to choose corn plants are : so many the damage of consumer to animal feed, work way of corn plants are easier than rice plants and the profits are received by farmers of these corn plants are greater, 3) fullfilment of economic needs of farmers, farmers can set aside a portion of proceeds corn good for saving. Farmers began to eagerly send their children to a higher level. Increase public awareness of their health, because they have more money to the clinic to seek treathment when they got sick and the farmers can build their own home to family and their in laws do not live at home. Keywords: The Social Ekonomic Behaviour, Corn Farmers.